Unveiling Sushi, a High-Quality Unique and Aesthetic Culinary - Ni Desak Made Santi Diwyarthi (Westscience Press, 2024)
This research is a qualitative study on sushi dishes, using a phenomenological approach based on experiences in sushi preparation, deep interview, and literature study. To reduce subjective bias in qualitative research, data triangulation method based on Moleong's theory is employed. The research findings indicate that sushi faces constraints in terms of shortages and obstacles to global development. Sushi has the strength and the weaknesses’ aspect. Sushi has the opportunity for maximum growth by implementing innovative technologies. The unique and aesthetic aspects of sushi include the variety of ingredients, the preparation in rice, the presentation, the serving style, the cultural significance the seasonal variation, the skill and technique, the umami flavour, customization, and eating experience.